Analysis of the current procedure for the creation and management of subjects with virtual component of the UNED of Costa Rica and proposal for improvement (Revista Electrónica Calidad en la Educación Superior, 2020)
This article analyses the current process for creating subjects with a virtual component at the State Distance University (UNED) in Costa Rica, and confronts the guidelines regarding the characteristics that the resources that will make up the modular teaching unit must possess (UDM) of each subject of this type. Consequently, a set of actions is proposed to strengthen the current procedure for creating and managing subjects with a virtual component: (1) teacher training in the planning and implementation of subjects with a virtual component as a requirement for its opening, (2) compilation of punctual and detailed information by the academic offer committee about the resources to include in the platform, (3) analysis and evaluation of the pedagogical mediation of the materials proposed for the subjects with a virtual component and (4) selection and prioritization of resources to be produced, jointly, with the DPMD.
Keywords: Distance education; online learning; pedagogical mediation; teaching materials